Treadmill exercise ameliorates social isolation-induced depression through neuronal generation in rat pups - Cho, Jung-Wan; Jung, Sun-Young; Lee, Sang-Won; Lee, Sam-Jun; Seo, Tae-Beom; Kim, Young-Pyo; Kim, Dae-Young (Journal of exercise rehabilitation, 2017)
Social isolation is known to induce emotional and behavioral changes in animals and humans. The effect of treadmill exercise on depression was investigated using social isolated rat pups. The rat pups in the social isolation groups were housed individually. The rat pups in the exercise groups were forced to run on treadmill for 30 min once a day from postnatal day 21 to postnatal day 34. In order to evaluate depression state of rat pups, forced swimming test was performed. Newly generated cells in the hippocampal dentate gyrus were determined by 5-bromo- 2’-deoxyuridine (BrdU) immunohistochemistry. We examined the expression of 5-hydroxytryptamine (5-HT) and tryptophan hydroxylase (TPH) in the dorsal raphe using immunofluorescence. The expression of brain-derived neurotrophic factor (BDNF) and tyrosine kinase B (TrkB) was detected by Western blot analysis. The present results demonstrated that social isolation increased resting time and decreased mobility time. Expression of 5-HT and TPH in the dorsal raphe and expression of BDNF and TrkB in the hippocampus were decreased by social isolation. The number of BrdU-positive cells in the hippocampal dentate gyrus was suppressed by social isolation. Treadmill exercise decreased resting time and increased mobility in the social isolated rat pups. Expression of 5-HT, TPH, BDNF, and TrkB was increased by treadmill exercise. The present results suggested that treadmill exercise may ameliorates social isolation-induced depression through increasing neuronal generation.